ADOBE FLASH MEDIA DEVELOPMENT DEVELOPMENT OF ADOBE FLASH MEDIA LEARNING THEMATIC LOCAL WISDOM SOUTH MALANG FOR STUDENTS INCLUSION - Tety Nur Cholifah (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
This meaning is motivated by the low use of Adobe Flash thematic learning media for learning because each teacher is fixated on conventional learning as well as the low student knowledge about local wisdom around the area of ​​residence. The goal is to produce interesting media and test the effectiveness of the media as material in teaching. This research is an R&D research that adapted the Borg & Gall (1983) development model with a 10-step procedure. There are two research designs, namely preliminary field trials and main field trials. The research subjects were elementary school students in class IV inclusion in the 2018/2019 school year in Malang. Data collection techniques using interview techniques, questionnaires, and tests. Analysis of the data used is qualitative and quantitative analysis. The results of this study are providing very good interest for students so that students' insights and learning outcomes have increased. This is supported by the results of the assessment in the main field trials cognitive aspects, affective aspects, and psychomotor aspects all in the